Respostas
respondido por:
2
x²+3x-6=-8
x²+3x-6+8=0
x²+3x+2=0
1) Calculando o Δ da equação completa:
Δ = b² - 4.a.c
Δ = 3² - 4 . 1 . 2
Δ = 9 - 4. 1 . 2
Δ = 1
Há 2 raízes reais.
2) Aplicando Bhaskara:
x = (-b +- √Δ)/2a
x' = (-3 + √1)/2.1 x'' = (-3 - √1)/2.1
x' = -2 / 2 x'' = -4 / 2
x' = -1 x'' = -2
S = (-2,-1)
x²+3x-6+8=0
x²+3x+2=0
1) Calculando o Δ da equação completa:
Δ = b² - 4.a.c
Δ = 3² - 4 . 1 . 2
Δ = 9 - 4. 1 . 2
Δ = 1
Há 2 raízes reais.
2) Aplicando Bhaskara:
x = (-b +- √Δ)/2a
x' = (-3 + √1)/2.1 x'' = (-3 - √1)/2.1
x' = -2 / 2 x'' = -4 / 2
x' = -1 x'' = -2
S = (-2,-1)
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás